Nyanyian Katoneng-Katoneng dalam Upacara Cawir Metua di Desa Serbajadi, Sunggal Kabupaten Deli Serdang - Piona Br Sembiring; Heristina Dewi; Sapna Br Sitopu (FKIP, Universitas Palangka Raya, 2026)
Katoneng-katoneng songs are an important element in the Karo community’s cawir metua funeral ceremony, a traditional ritual performed when a person dies at an advanced age after completing all stages of customary life. In this ceremony, katoneng-katoneng serves not only as musical accompaniment but also as a medium for conveying customary, emotional, and symbolic messages. This study focuses on the functions of katoneng-katoneng in the cawir metua ceremony and examines the musical forms and structures used in its performance. The research aims to explain how musical elements and textual content support the ritual process and construct social and cultural meanings for the Karo community. This study uses a descriptive analytical method through field observation, interviews, audio-visual recording, musical transcription, and structural analysis. The analysis is guided by Koentjaraningrat’s cultural anthropology framework, Alan P. Merriam’s theory of musical functions, and the semiotic theories of Ferdinand de Saussure and Roland Barthes. The results show that katoneng-katoneng has seven main functions: aesthetic appreciation, entertainment, communication, symbolism, reinforcement of social norms, cultural continuity, and social integration. Thus, katoneng-katoneng preserves and strengthens Karo cultural identity.